Effect of sodium bicarbonate on tooth surface roughness and microhardness - Erma Mahmiyah; Amakhul Husna; Rusmali Rusmali (Poltekkes Kemenkes Bandung, 2026)
ABSTRACT Background: Baking soda is an abrasive agent widely used to remove dental plaque and stains through mechanical friction on the enamel surface. Objective: This study aimed to evaluate the effect of different baking soda concentrations on tooth surface roughness and microhardness to identify a formulation that is both effective and clinically safe. Methods: This study was an in vitro experimental study using a Post-Test Only Control Group Design with 36 extracted human teeth divided into control and treatment groups. The specimens were exposed to sodium bicarbonate paste at concentrations of 35%, 50%, and 70%. The paste was applied for three minutes, brushed in a circular motion eight times, and then rinsed. The procedure was repeated four times, simulating once-weekly application over four weeks. Surface roughness was measured using a Surface Roughness Tester (Starrett), while tooth microhardness was assessed using a Vickers Hardness Tester (Shimadzu F0310). Results: One-way ANOVA analysis revealed significant differences in surface roughness among groups (p<0.05), with the 70% concentration showing a significantly higher roughness compared to the control and 35% groups. Microhardness analysis also showed a statistically significant difference overall (p<0.05); however, post hoc testing revealed no significant differences among the treatment groups. Conclusion: Clinically, these findings indicate that sodium bicarbonate at concentrations of 35% and 50% does not compromise enamel integrity, as it does not increase surface roughness or reduce tooth microhardness, supporting its potential application in toothpaste formulations for safe plaque and stain removal.